Black women in Latin America and the Caribbean : critical research and perspectives - Medeiros, Melanie A.; Perry, Keisha-Khan Y.; Smith, Christen A., 1977-; Abdalla, Julia S.; Crumdy, Angela; Pereira, Bruna Cristina Jaquetto; Gordon-Ugarte, Ishan; Hernández Reyes, Castriela Esther; Lewis, Eshe; Rodrigues, Cristiano (Rutgers University Press, 2023)
"Black Women in Latin America and the Caribbean: Critical Research and Perspectives employs an intersectional and interdisciplinary approach to examine Black cisgender women's social, cultural, economic, and political experiences in Latin America and the Caribbean. It presents the results of critical empirical research emphasizing Black women's innovating, theoretical, and methodological approaches to activism and class-based gendered racism and Black politics. While there are a few single-authored books focused on Black women in Latin American in Caribbean in specific, the vast majority of the scholarship on Black women in Latin America and the Caribbean has been published as theses, dissertations, articles, and book chapters. This volume situates these social and political analyses as interrelated and dialogic and contributes a transnational perspective to contemporary conversations surrounding the continued relevance of Black women as a category of social science inquiry. When read together, the chapters offer a hemispheric framework for understanding the lasting legacies of colonialism, transatlantic slavery, plantation life, and persistent socio-economic and cultural violence"--